2014
DOI: 10.1007/s12307-013-0142-2
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles mediated cross-talk between tumoral and endothelial cells promote the constitution of a pro-metastatic vascular niche through Arf6 up regulation

Abstract: The tumor stroma plays an essential role in tumor growth, resistance to therapy and occurrence of metastatic phenotype. Tumor vessels have been considered as passive conducts for nutrients but several studies have demonstrated secretion of pro-tumoral factors by endothelial cells. The failure of anti-angiogenic therapies to meet expectations raised by pre-clinical studies prompt us to better study the cross-talk between endothelial and cancer cells. Here, we hypothesized that tumor cells and the endothelium se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 75 publications
(98 reference statements)
4
50
0
Order By: Relevance
“…It was shown that miR-503 inhibits PI3Kp85 and IKKβ and consequently, Akt phosphorylation and NFκB activation (Yang et al 2014). In agreement with this, our group and others have demonstrated that activation of these signaling pathways by MPs confers a resistance phenotype (de Souza et al 2015;Pasquier et al 2014;Wysoczynski and Ratajczak 2009). miRNA-503 downregulation was also observed in lung and hepatocellular cancers and in highly invasive breast cancer cells, and its overexpression induces G1 arrest, reduces cell migration and invasiveness in vitro and in vivo (Gong et al 2014;Yang et al 2014;Zhou and Wang 2011).…”
Section: Microparticles and Micrornassupporting
confidence: 84%
See 3 more Smart Citations
“…It was shown that miR-503 inhibits PI3Kp85 and IKKβ and consequently, Akt phosphorylation and NFκB activation (Yang et al 2014). In agreement with this, our group and others have demonstrated that activation of these signaling pathways by MPs confers a resistance phenotype (de Souza et al 2015;Pasquier et al 2014;Wysoczynski and Ratajczak 2009). miRNA-503 downregulation was also observed in lung and hepatocellular cancers and in highly invasive breast cancer cells, and its overexpression induces G1 arrest, reduces cell migration and invasiveness in vitro and in vivo (Gong et al 2014;Yang et al 2014;Zhou and Wang 2011).…”
Section: Microparticles and Micrornassupporting
confidence: 84%
“…In addition, Pasquier and colleagues showed the importance of ARF6 upregulation in MPs in mediating a vascular metastatic microenvironment. Inhibition or deletion of ARF6 triggered a reduction in MP shedding by endothelial and cancer cells (Pasquier et al 2014). Furthermore, Schllienger et al (2014 demonstrated that ARF1 activity is required for the shedding of MPs, invadopodia maturation and MMP-9 activity, suggesting that ARF1 is important not only to MP biogenesis but also to MP-mediated cancer cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, it was demonstrated that EV isolated from tumor cells with a mesenchymal or EMT phenotype activated recipient EC to a much larger extent than EV from epithelial tumor cells. In addition, activated EC-derived EV were more tumorigenic than normal EC-derived EV, suggesting a positive enforcement of tumor growth and angiogenesis through EV (Pasquier et al, 2014). This way, tumors would have the ability to systemically condition the endothelium to create premetastatic niches by activating multiple signaling pathways through EV secretion.…”
Section: F Emerging Mechanisms Of Resistancementioning
confidence: 99%